In vitro and in silico studies reveal antidiabetic properties of arylbenzofurans from the root bark of Morus mesozygia Stapf - Olufolabo, Katherine Olabanjo; Lüersen, Kai; Oguntimehin, Samuel Ayoolu; Nchiozem-Ngnitedem, Vaderament-A.; Agbebi, Emmanuel Ayodeji; Faloye, Kolade Olatubosun; Nyamboki, Divinah Kwamboka; Rimbach, Gerald; Matasyoh, Josphat Clement; Schmidt, Bernd; Moody, Jones Olanrewaju (Frontiers in Pharmacology, 2024)
Diabetes remains an important disease worldwide with about 500 million patients globally. In tropical Africa, Morus mesozygia is traditionally used in the treatment of diabetes. Biological and phytochemical investigation of the root bark extracts of the plant led to the isolation of a new prenylated arylbenzofuran named 7-(3-hydroxy-3-methylbutyl)moracin M (1) and two congeners, moracins P (2) and M (3). When compared to acarbose (IC50 = 486 µM), all the isolated compounds are better inhibitors of α-glucosidase with in vitro IC50 values of 16.9, 16.6, and 40.9 µM, respectively. However, they were not active against α-amylase. The compounds also demonstrated moderate inhibition of dipeptidyl peptidase-4 (DPP4). Based on in silico docking studies, all isolates (1, 2, and 3) exhibit binding affinities of -8.7, -9.5, and -8.5 kcal/mol, respectively against α-glucosidase enzyme (PDB: 3AJ7). They are stabilized within the α-glucosidase active site through hydrogen bonds, pi interactions, and hydrophobic interactions. This study provides scientific support for the traditional use of M. mesozygia in the treatment of diabetes as well as adding to the repository of α-glucosidase inhibitory agents.